Use of cardanol derivatives as plasticizers for PVC. (28th November 2016) - Greco, Antonio; Ferrari, Francesca; Del Sole, Roberta; Maffezzoli, Alfonso
Abstract : This work is aimed to study the suitability of cardanol derivatives as plasticizers for poly(vinyl chloride), (PVC). The plasticizers are obtained by chemical modification of cardanol, a natural, renewable resource, obtained as a by‐product of the cashew nut shell industry. Due to the choice of environmentally friendly chemical modification routes, partial conversion of cardanol to the target compounds was obtained. Consequently, the tested plasticizers were composed of a mixture of different cardanol derivatives. Rheological tests on PVC plastisols obtained with neat cardanol showed that cardanol must be subjected to chemical modifications, such as acetylation and epoxidation, in order to perform as an effective plasticizer. In particular, only after epoxidation, does the cardanol derivative become fully soluble in PVC. PVC plastisols obtained with such cardanol derivatives present a similar gelation temperature compared to bis (2‐ethylhexyl) phthalate (DEHP) based plastisols. Mechanical properties of the flexible PVC produced by the addition of cardanol derived plasticizer after epoxidation are also comparable to those attained by the use of DEHP. Nevertheless ageing tests showed an accelerated migration of cardanol derived plasticizer, attributed to the loss of unreacted cardanol present in the plasticizer, which was in turn responsible for a significantly faster degradation of the properties, compared to flexible PVC containing DEHP. This highlights the relevance of achieving a high yield of the acetylation and epoxidation reactions, which is a relevant issue of the future research and development activities in this field. J. VINYL ADDIT. TECHNOL., 24:E62–E70, 2018. © 2016 Society of Plastics Engineers